Video head impulse testing in patients with isolated (hemi)nodular infarction - Lee, Seung-Han; Kim, Jae-Myung; Kim, Joon-Tae; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2023)
Background Isolated (hemi)nodular strokes as underlying cause of acute dizziness are rare, thus there are still gaps of knowledge in the clinical presentation of affected patients. Clinical and experimental evidence has suggested that lesions involving the nodulus lead to various vestibulo-ocular deficits including prolonged velocity-storage, periodic-alternating nystagmus, positional nystagmus, abolished suppression of post-rotatory nystagmus by head-tilt and impaired verticality perception. At the bedside, the angular vestibulo-ocular reflex (aVOR), as assessed by the horizontal head-impulse test (HIT), has been reported to be normal, however quantitative assessments of all six semicircular canals are lacking. Objective The primary aim of this case series was to characterize the spectrum of clinical presentations in isolated (hemi)nodular strokes. Furthermore, based on preliminary observations, we hypothesized that the aVOR is within normal limits in isolated nodular strokes. Methods We retrospectively included patients with isolated (hemi)nodular stroke on diffusion-weighted MR-imaging from a prospective stroke-registry. All patients received a standardized bedside neuro-otological assessment and quantitative, video-based HIT (vHIT) of all six semicircular canals. Overall ratings of vHIT (normal vs. abnormal function) were performed independently by two reviewers and disagreements were resolved. Results Between January 2015 and December 2021 six patients with isolated nodular (n = 1) or heminodular (n = 5) ischemic stroke were included. Clinical presentation met diagnostic criteria for acute vestibular syndrome (AVS) in 5/6 patients and for episodic vestibular syndrome (EVS) in 1/6 patients. Ocular motor abnormalities observed included the presence of spontaneous horizontal nystagmus (n = 2), positional nystagmus (5/6), head-shaking nystagmus (3/6), skew deviation (n = 1), and moderate or severe truncal ataxia (5/6). Bedside HIT was normal in all patients and no gaze-evoked or periodic alternating nystagmus was observed. aVOR-gains were within normal range in all patients and overall aVOR-function as assessed by vHIT was rated as normal in all six patients. Conclusions Using quantitative, video-based testing of the horizontal and vertical aVOR, preserved integrity of the aVOR in (hemi)nodular strokes was confirmed, extending preliminary findings at the bedside. Furthermore, widespread deficits of both ocular stability, postural control and volitional eye movements were observed in our study cohort, being consistent with findings reported in previous studies.